Measures for Building Lighting Performance in Malaysian Historical Buildings: A Systematic Review - Kamaruzzaman, Syahrul Nizam; Zulkifli, Nursyahida (Journal of Surveying, Construction and Property, 2014)
Developing countries, including Malaysia, focus on sustainable development. Development in our country should consider all the elements of sustainability in order to support the government effort as stated in the Ninth Malaysian Plan. Over the past five years, there has been a move away from constructing new buildings to refurbishing older ones. This is the meta-data analysis to review and evaluates the approach to the refurbishment of lighting and analyzes the existing energy efficiency policy and measures, for future improvement in energy efficiency in this type of building. This paper aims to assess the characteristics of electricity use and to identify specific information for potential energy conservation in lighting. The main sources of this literature review are journal articles, and internet searches. The study found that lighting building performance is measured by daylighting, lighting simulation and automatic lighting systems. Occupant satisfaction is another measure to determine the lighting performance in the building. This study adds to knowledge from the perspective of lighting performance. It offers new and valuable insights to enable Malaysia to achieve optimum energy efficiency, with financial savings as well as reducing the environmental impact.